(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines didactic material as a means of teaching Russian. Russian language at school is determined by two factors: the subject of study and the objectives of study. The ability to master subjects is not the same. Methodological literature pays attention to the topic related to the use of didactic material as a special type of teaching aids (maps, tables, sets of cards with text, etc.). Didactic material is a necessary teaching tool and an assistant for conducting lessons in accordance with the logic proposed by the textbook.